Staphylococcus aureus Bloodstream Infection in Patients With Prosthetic Joints in the Prospective VIRSTA Cohort Study: Frequency and Time of Occurrence of Periprosthetic Joint Infection. (5th December 2019) - Dufour, Sébastien; Piroth, Lionel; Chirouze, Catherine; Tattevin, Pierre; Becker, Agathe; Braquet, Pierre; Ferry, Tristan; Duval, Xavier; Le Moing, Vincent
Abstract: Among 143 patients of the VIRSTA cohort study with Staphylococcus aureus bacteremia and an arthroplasty implanted for more than a year, S. aureus periprosthetic joint infection was observed in 19%. Signs of infection (pain and swelling) were always present, in median 1 day (range, 0–21 days) after onset of bacteremia. Staphylococcus aureus has both a high potential for metastatic infection and a high affinity for foreign material. Possible prosthesis infection is of clinical concern in all patients with preexisting prosthetic materials experiencing S. aureus bloodstream infection (SAB). Prosthetic joints are especially prone to infection during the course of bacteremia, with a risk of infection much higher with S. aureus than with other microorganisms, 20% vs 7%, in a recent prospective study [1 ]. As early intervention with debridement in prosthetic joint infection (PJI) is paramount to retain the implant and to prevent infection relapse; eliminating PJI after SAB is important. However, additional data are needed to better describe the clinical characteristics of PJI after SAB in particular time lapses and whether systematic imaging of the prosthesis could be necessary after SAB. We described the frequency and clinical presentation of PJIs observed among patients with prosthetic joints implanted for >1 year before bacteremia and enrolled in the VIRSTA study, a multicenter prospective cohort study of patients with SAB.